Analyzing the Mechanical Performance of Solid Oxide Fuel Cells at Interfacial Anode/Electrolyte Regions Using Sub-Micron Resolution 3D X-Ray Computed Tomography. (30th May 2017) - Heenan, Thomas M. M.; Robinson, James B.; Lu, Xuekun; Bailey, Josh J; Brett, Daniel J.L.; Shearing, Paul R.
Abstract : An inability to withstand rapid thermal cycling remains a shortcoming of the solid oxide fuel cell, resulting in start-up and shut-down times being prohibitively long. This work utilizes sub-micron resolution 3D X-ray CT reconstructions of a particularly problematic region due to a difference in thermal expansion properties within SOFCs: the anode-electrolyte interface. By examining the effects of thermal shock in 3D, this work improves the understanding of the causes and effects of mechanical dynamics which are attributed to losses in electrochemical performance.